Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/28
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Approach to Activity Selection

Abstract: The general task of finding an assignment of agents to activities under certain stability and rationality constraints has led to the introduction of two prominent problems in the area of computational social choice: Group Activity Selection (GASP) and Stable Invitations (SIP). Here we introduce and study the Comprehensive Activity Selection Problem, which naturally generalizes both of these problems. In particular, we apply the parameterized complexity paradigm, which has already been successfully employed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…SGASP is fixed-parameter tractable when parameterized by t + a. This is the only fixed-parameter tractability result presented in the paper, and is essentially tight: it was recently shown that SGASP is W [1]-hard when parameterized by a alone [9], and the W [1]-hardness of the problem when parameterized by t is obtained in this paper. Our first step towards obtaining the desired fixed-parameter algorithm for SGASP is to show that every YES-instance has a solution which is acyclic-in particular, a solution with no cycles formed by interactions between activities and agent types (captured in terms of the incidence graph G of an assignment).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…SGASP is fixed-parameter tractable when parameterized by t + a. This is the only fixed-parameter tractability result presented in the paper, and is essentially tight: it was recently shown that SGASP is W [1]-hard when parameterized by a alone [9], and the W [1]-hardness of the problem when parameterized by t is obtained in this paper. Our first step towards obtaining the desired fixed-parameter algorithm for SGASP is to show that every YES-instance has a solution which is acyclic-in particular, a solution with no cycles formed by interactions between activities and agent types (captured in terms of the incidence graph G of an assignment).…”
Section: Introductionmentioning
confidence: 53%
“…It is therefore natural to study these problems through the lens of parameterized complexity [8,2]. Apart from parameterizing by the solution size (i.e., the number of agents assigned to any activity in a solution) [19], the perhaps most prominent parameterizations thus far have been the number of activities, the number of agents, and in the case of gGASP structural parameterizations tied to the structure of the network such as treewidth [6,18,15,9]. Consequently, the parameterized complexity of all three variants of GASP w.r.t.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work is also related to models from cooperative game theory, such as hedonic games [11,22,5] and group activity selection games [19,18,21]. In hedonic games, the agents form coalitions and their utilities are decided solely by the members in the coalition, without any resource in the model.…”
Section: Related Workmentioning
confidence: 99%
“…Apart from requiring non-trivial insight into the structure of a possible solution, the approaches used to solve the Boehmer and Elkind (2020a): when the number of colors (γ) is 2, is Nash-stable HDG fixed-parameter tractable when parameterized by the size of the smaller color class? Here, we provide a highly non-elementary reduction from a variant of the GROUP ACTIVITY SELECTION problem (Darmann et al 2017;Eiben, Ganian, and Ordyniak 2018) which excludes fixed-parameter tractability.…”
Section: Introductionmentioning
confidence: 99%